2016
DOI: 10.1007/s11141-016-9688-4
|View full text |Cite
|
Sign up to set email alerts
|

Features of the Electromagnetic and Plasma Disturbances Induced at the Altitudes of the Earth’s Outer Ionosphere by Modification of the Ionospheric F 2 Region Using High-Power Radio Waves Radiated by the SURA Heating Facility

Abstract: International audienceIn this paper we systematize the results of studying the characteristics of the plasma-density ducts, which was conducted in 2005–2010 during the DEMETER-satellite operation. The ducts are formed at altitudes of about 700 km as a result of the ionospheric F2 region modification by high-power high-frequency radio waves radiated by the midlatitude SURA heating facility. All the performed measurements are used as the basis for determining the formation conditions for such ducts, the duct cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…These fluctuations correspond to the 10–15 km spatial scale of the HF‐induced plasma irregularities. (Note that similar scales were previously detected by DEMETER (Frolov et al, )).…”
Section: Conjugate Sura‐swarm Experimentssupporting
confidence: 86%
See 1 more Smart Citation
“…These fluctuations correspond to the 10–15 km spatial scale of the HF‐induced plasma irregularities. (Note that similar scales were previously detected by DEMETER (Frolov et al, )).…”
Section: Conjugate Sura‐swarm Experimentssupporting
confidence: 86%
“…Depending on the configuration of the orbit, spacecrafts observed the effect at different altitudes from the topside ionosphere to the magnetosphere (Streltsov et al, and references therein). Large scale plasma ducts caused by the HF heating were detected during the conjugate experiment of the SURA heating facility and the DEMETER satellite, which measured the electron and ion temperatures and densities along its trajectory in the vicinity of the HF transmitter (Frolov et al, , ; Rapoport et al, ). It was shown that the regions of enhanced electron concentration are formed due to the upward drift and removal of plasma from the heating region, which is below the 660 km altitude DEMETER orbit (Milikh et al, ; Vartanyan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of this program was to study the formation, structure and characteristics of ducts in the heated ionosphere and their role in ionosphere-magnetosphere coupling and VLF wave propagation. An overview of the results obtained during the DEMETER joint program was given by Frolov et al, [2016] and references therein.…”
Section: Demeter Satellitementioning
confidence: 99%
“…SURA, as the old HF heating facility, has been operated since 1981. Many active experiments were conducted at SURA, including DEMETER, DMSP, CASSIOPE/e‐POP, and SWARM satellites (Frolov et al, 2008a, 2008b, 2016, 2018; James et al, 2017; Zhang et al, 2016), in which many related phenomena have been studied such as conditions for determining the formation of artificial ducts, an influence of pumping modes on turbulence features, HF heating mechanisms, and pumping wave (PW) ray tracing.…”
Section: Introductionmentioning
confidence: 99%